A Dual Plating Battery with the Iodine/[ZnIx(OH2)4−x]2−x Cathode. (20th September 2019) - Hong, Jessica J.; Zhu, Liangdong; Chen, Cheng; Tang, Longteng; Jiang, Heng; Jin, Bei; Gallagher, Trenton C.; Guo, Qiubo; Fang, Chong; Ji, Xiulei
Abstract: Plating battery electrodes typically deliver higher specific capacity values than insertion or conversion electrodes because the ion charge carriers represent the sole electrode active mass, and a host electrode is unnecessary. However, reversible plating electrodes are rare for electronically insulating nonmetals. Now, a highly reversible iodine plating cathode is presented that operates on the redox couples of I2 /[ZnI x (OH2 )4− x ] 2− x in a water‐in‐salt electrolyte. The iodine plating cathode with the theoretical capacity of 211 mAh g −1 plates on carbon fiber paper as the current collector, delivering a large areal capacity of 4 mAh cm −2 . Tunable femtosecond stimulated Raman spectroscopy coupled with DFT calculations elucidate a series of [ZnI x (OH2 )4− x ] 2− x superhalide ions serving as iodide vehicles in the electrolyte, which eliminates most free iodide ions, thus preventing the consequent dissolution of the cathode‐plated iodine as triiodides. Abstract : Eine hochreversible Iod‐Plating‐Kathode arbeitet mit dem Redoxpaar I2 /[ZnI x (OH2 )4− x ] 2− x in einem Wasser‐in‐Salz‐Elektrolyt. Die Kathode, mit einer theoretischen Kapazität von 211 mAh g −1, ist auf Kohlefaserpapier als Stromkollektor aufgebracht, wodurch eine große Flächenkapazität von 4 mAh cm −2 erzielt wird.